Hydrogen‐Mediated C−C Bond Formation: Stereo‐ and Site‐Selective Chemical Synthesis Beyond Stoichiometric Organometallic Reagents. Issue 1 (5th October 2017) - Schwartz, Leyah A.; Krische, Michael J.
Abstract: Stereo‐ and site‐selective methods for the byproduct‐free modification of unprotected organic compounds that occur through the addition or redistribution of hydrogen are natural endpoints in the advancement of methods for efficient chemical synthesis. Progress toward this goal requires a departure from reactants that embody non‐native structural elements, including stoichiometric organometallic reagents, directing/protecting groups and chiral auxiliaries. In this perspective, we highlight how hydrogen‐mediated C−C bond formations developed in our laboratory have enabled progress toward ideal chemical syntheses of this type. Abstract :